PENGARUH KOMPENSASI, LINGKUNGAN KERJA, DAN MOTIVASI TERHADAP KINERJA KARYAWAN (Studi Kasus pada BAPPEDA Kota Magelang dan DISKOMINSTA Kota Magelang) - Enggarwati, Dewi Sari (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kota Magelang, 2023)
The background of this research is Human Resource Management (HR) the management of human resources to achieve company goals. This study aims to examine and analyze the effect of compensation, work environment and motivation on employee performance. The population used in this study were 50 employees of Bappeda and Diskominsta Magelang City. The sampling method used the saturated sample method with a total of 50 respondents. The analytical tool used in this study is multiple regression analysis with support of the SPSS program. The results of this study indicate that compensation, work environment, and motivation have a simultaneous effect on employee performance. Compensation has a significant positive effect on employee performance. The work environment has a significant positive effect on employee performance. Motivation has a significant positive effect on employee performance.